Tvorivosť v procese prezentácie architektonického dedičstva - Petrášová, Silvia (Akademické nakladatelství CERM, 2013)
Experts have been wondering to what extent the work of architects in monument restoration requires creativity and whether this task must be appointed to architects. There is also a conflict between monument preservation and new production, when historical environment is not seen for its potential but perceived as a problem. This is caused by the lack of cultural identity and clash of consumer society and spiritual values. Quality presentation of architectural heritage is a precondition for positive change. Key positions in this process are a methodologist – the author of the proposal for restoration or a regional monuments board officer, and an architect – the author of the project. They are translating scientific outcomes of an architectural monument research into its future presentation. Key terms in efforts to achieve a positive shift in the process of presenting architectural heritage are specialization, interdisciplinary cooperation and coordination. Specialization should be required from both architects and methodologists. However, no institutions or laws demand that. Interdisciplinary cooperation is teamwork. While it has potentials and risks, it is an essential element of this complex issue, assuring creative process with positive results. Coordination should be done by an architect, given all the professions involved – his or her education provides for technical, functional and artistic elements of architectural work. However, for optimal presentation it is not decisive whether it is an architect or any other educated person. Despite complex conditions, there are some presentations of architectural heritage where the process allowed for ideal implementation. The question is whether we will continue to hope for such cases, or instead we will contribute to maximizing them...

V odborných kruhoch v oblasti architektúry rezonuje otázka, do akej miery je práca architekta pri obnove architektonickej pamiatky tvorivá, či je vôbec nutné, aby túto funkciu zastával architekt. Zároveň dochádza ku konfliktu medzi ochranou pamiatok a novou tvorbou, keď nie je historické prostredie chápané ako potenciál, ale ako problém. Dôvodom je nedostatočná kultúrna identita a kríza vzťahov medzi konzumnou spoločnosťou a duchovnými hodnotami. Kvalitná prezentácia architektonického dedičstva je predpokladom pozitívnej zmeny.
Creativity in the process of presenting architectural heritage
Keywords: prezentace architektonického dědictví; proces; tvořivost; specializace; koordinace; presenting architectural heritage; process; creativity; specialization; coordination